Development of the cardinality principle in Macedonian preschool children - Nikoloska Ana (Psihologija, 2009)
Cardinality principle refers to the fact that the last number tag used in counting determines the cardinality of a set. Macedonian kindergarten children were tested with the give-a-number task for understanding of this principle. It was found that Macedonian children, unlike their western counterparts, pass through an additional stage, 5-knowers, before they master the cardinality principle. Also, the age at which they pass through the individual stages is somewhat higher than the age of children coming from western samples. Possible explanations are offered and discussed.